2007
DOI: 10.1158/1078-0432.ccr-07-1443
|View full text |Cite
|
Sign up to set email alerts
|

First in Human Phase I Trial of 852A, a Novel Systemic Toll-like Receptor 7 Agonist, to Activate Innate Immune Responses in Patients with Advanced Cancer

Abstract: Purpose: Recent advances in the understanding of innate immunity suggest that an orchestrated sequence of events is required to elicit a productive immune response against cancer. We studied the systemic administration of the Toll-like receptor 7 agonist 852A, a small-molecule imidazoquinoline, in patients with advanced cancer. Preclinical studies showed that 852A stimulates plasmacytoid dendritic cells to produce multiple cytokines, such as IFN-a, interleukin-1 receptor antagonist, and IFN-inducible protein-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
151
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(162 citation statements)
references
References 28 publications
6
151
0
3
Order By: Relevance
“…In contrast to the experience with solid tumor patients at similar doses, 6,7 no grade 3 toxicities were seen. Adverse effects reported most frequently were chills and 'hot flashes', which seemed to decrease with repeated injections.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…In contrast to the experience with solid tumor patients at similar doses, 6,7 no grade 3 toxicities were seen. Adverse effects reported most frequently were chills and 'hot flashes', which seemed to decrease with repeated injections.…”
mentioning
confidence: 62%
“…Patients in groups I, II and III were injected with 0.3, 0.45 and 0.6 mg/m 2 , respectively, because studies of solid tumor patients had established 1.2 mg/m 2 as the maximum tolerated dose for 852A. 7 Clinical responses were determined by standard National Cancer Institute (NCI) criteria.…”
mentioning
confidence: 99%
“…In spite of conflicting data on TLR expression in NK cells, several groups have shown that TLR7/TLR8 agonists induce NK cell activation, as judged by CD69 expression, IFN-␥ production, and exertion of their cytotoxic effector function. However, it was also observed that this TLR7/TLR8-induced NK cell activation is crucially dependent on contact with cytokines (e.g., IL-12 or type I IFNs) produced by accessory cells in peripheral blood [24,70,70,71,[73][74][75][76]. Therefore, it is not completely clear yet if the NK activation observed after the addition of TLR7/8 agonists is partially caused by or dependent on direct activation of TLR7 and/or TLR8 in NK cells.…”
Section: Cd8mentioning
confidence: 99%
“…These agonists (like stabilized ssRNA, R-848, and 852A) have now also been tested as IRMs in preclinical models [123] and in clinical trials [75,124,125]. Until now, TLR7/8 agonists were predominantly given by topical administration because of the side effects reported after oral and systemic therapy with IRMs [126 -129].…”
Section: Current Use Of Tlr7/8 Ligands In Cancer Treatment and Cancermentioning
confidence: 99%
See 1 more Smart Citation